The remarried empress. 3 - Alphatart (Novelist); HereLee (Mangaka) (Ize Press, 2023)
"Secrets and schemes are swirling around the palace ... and when people are playing with fire, someone's bound to get burned. Navier is doing her best to manage the flames, but when a magic potion leaves Grand Duke Kaufman spellbound, Sovieshu's misconceptions about her love life spiral out of control! Meanwhile, Rashta is all but fanning the inferno -- though if Duchess Tuania's admirer has his way, the mistress will soon face the consequences of her malicious ploys. And Heinrey's blazing passion for Navier may have to be put on the back burner when news of his brother's ill health reaches the Eastern Empire. Will the empress and prince be pulled apart before they can be pushed together...?"--Page 4 of cover.